1997
DOI: 10.1093/bja/78.5.618
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and second gas effects: can the accepted explanation be improved?

Abstract: During induction with high inspired concentrations of nitrous oxide, net uptake of gas produces a contraction in volume and a concentrating effect. In turn, this results in concentration and second gas effects. Most explanations of these effects are based on the common "rectangle" diagram devised by Stoelting and Eger and contain several inconsistencies which are explored here in order to produce a more accurate description. It is shown that in the standard diagram gas uptake is incomplete, there is ambiguity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
1
24
0
2
Order By: Relevance
“…The suggested scheme is also the most reliable in achieving mean end-expired concentration equal to 1 MAC (Table 2) after the first 2 min of isoflurane. It would be interesting to evaluate the effect of nitrous oxide, as its hypnotic properties would be especially useful in this context, although computer simulation would be complicated by the second gas effect [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…The suggested scheme is also the most reliable in achieving mean end-expired concentration equal to 1 MAC (Table 2) after the first 2 min of isoflurane. It would be interesting to evaluate the effect of nitrous oxide, as its hypnotic properties would be especially useful in this context, although computer simulation would be complicated by the second gas effect [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…Years later, Korman and Mapleson showed that the effect is primarily one of volume “shrinkage” and produced modifications of the Stoelting-Eger diagram that explained the phenomenon more accurately, including equilibration of the alveolar compartment with blood. 3 …”
mentioning
confidence: 99%
“…Finally, due to the pharmacological characteristics of the last inhaling anesthetics, together with the advantages offered by low flow or metabolic flow circuits, volatile anesthesia seems to be more advantageous than intravenous anesthesia, especially in regard to waking time and awareness prevention. (10,11) Technology …”
Section: Pharmacological Considerationsmentioning
confidence: 99%